Мотив воды в творчестве Марины Цветаевой - Янчук, Елена (Acta Polono-Ruthenica, 2021)
This article is devoted to the analysis of the motif of water in the works of Marina Tsvetaeva. The main goal is to trace how the concrete and simple lexeme “water” participates in the meaning-generating poetic process, and to prove the special significance of this motif as an important sign of her creative thinking, worldview and creative personality in general. The article uses extensive material (about 630 examples) taken from poetic and prose texts to consider the main meanings of the motif of water and its functional features in the individual author’s viewpoint. Water, without losing its natural concreteness, becomes one of the important tools for metaphorizing the processes and phenomena of not only the physical, but also the spiritual world of the poet.